Battered women: self-defence and provocation - Oswell, Bennita-Simone (Institute of Criminology, 2024)
The act of 'being battered' is within the realm of experience of many women and may involve not only actual physical assault but also psychologically debilitating practices, all of which occur in a society which seems to be unable to realise the extent of the problem. 'Wife beating' has always been deemed to be a personal, family problem, to be solved by the wife to the best of her abilities - it is seen as an internal family issue, not the business of neighbours or outsiders and certainly not within the purview of the police or the law. The view therefore held by friends, neighbours and the police has generally been that these women 'encourage, elicit and enjoy this type of abuse'.